(untitled) (Filološke studije, 2019)
According to the systematic approach the scientific text is a complicated system of subtexts which reflect the ontology, methodology, and axiology, reflective and pragmatic components of the scientist cognitive activity. An important extralinguistic factor, determining pragmatic content of the text is the “addressee-factor”. The article reviews the manifestation of this factor in Russian scientific texts. Linguistic units, which represent pragmatic information, should be combined in a specific text substructure – the subtext of addressing. This subtext is redundant for the formation of the cognitive content of the text, but it is necessary for the exposition of the scientific content, i.e. its presentation for the reader according to the standards of scientific style, because due to it the reader gets oriented in the text. The article reviews various types of operators of pragmatic information – cliché units, which “pack” the cognitive content. Some of these units reflect prospect and retrospect of exposition, others limit the problem of research, and the third activate the reader’s mind and involve him into dialogue with the author of the text. In addition to the above, the units of addressing provide for the cohesion of the overall text. On the whole, the subtext of addressing is a universal pragmatic means of scientific knowledge representation.